Faktor-faktor yang mempengaruhi kinerja usaha muslimpreneur di Kota Batam - Sumarni, Mei; Hati, Shinta Wahyu (Fakultas Ekonomi, UIN Maliki Malang, 2019)
This study aims to determine what factors are considered Muslim entrepreneurs in determining the business performance of a Muslimpreneur in the city of Batam. Techniques of collecting data using kuisoner, observation, and documentation. Test the research instrument by using the validity and reliability analysis. Data analysis method used in this research is descriptive analysis and confirmatory factor analaisis (CFA). The result of the research shows 4 variables forming the business performance of a Muslimpreneur namely Human Resources, Marketing, Finance, and Production. While the most dominant factor considered by employers in determining the performance of a muslimpreneur in Batam City is the production and human resources with the value of variance of 0.23% and 1.45%.